Evidence for hope : the search for sustainable development : the story of the International Institute for Environment and Development - Cross, Nigel, 1953- (Earthscan Publications, 2003)
Since the Stockholm Environment Conference in 1972 and the Rio Summit in 1992, there has been unprecedented public concern for the future of the planet and a growing awareness that development needs to be sustainable. This text charts the growth of these ideas by beginning with a visionary piece written by Barbara Ward in the 1970s, and ends with a chapter looking ahead another 30 years into the future.; Two generations of thinkers and activists have helped to shape environment and development policy and increase local level power in environmental management. In celebration of their 30th anniversary, the IIED's most influential writers, in this volume, provide a perspective on three decades of development and green debates.